Eicosanoid Biosynthesis in Male Reproductive Development: Effects of Perinatal Exposure to NSAIDs and Analgesic Drugs - Tran-Guzman, Amy; Culty, Martine (Frontiers in Toxicology, 2022)
Increasing rates of infertility associated with declining sperm counts and quality, as well as increasing rates of testicular cancer are contemporary issues in the United States and abroad. These conditions are part of the Testicular Dysgenesis Syndrome, which includes a variety of male reproductive disorders hypothesized to share a common origin based on disrupted testicular development during fetal and neonatal stages of life. Male reproductive development is a highly regulated and complex process that relies on an intricate coordination between germ, Leydig, and Sertoli cells as well as other supporting cell types, to ensure proper spermatogenesis, testicular immune privilege, and endocrine function. The eicosanoid system has been reported to be involved in the regulation of fetal and neonatal germ cell development as well as overall testicular homeostasis. Moreover, non-steroidal anti-inflammatory drugs (NSAIDs) and analgesics with abilities to block eicosanoid synthesis by targeting either or both isoforms of cyclooxygenase enzymes, have been found to adversely affect male reproductive development. This review will explore the current body of knowledge on the involvement of the eicosanoid system in male reproductive development, as well as discuss adverse effects of NSAIDs and analgesic drugs administered perinatally, focusing on toxicities reported in the testis and on major testicular cell types. Rodent and epidemiological studies will be corroborated by findings in invertebrate models for a comprehensive report of the state of the field, and to add to our understanding of the potential long-term effects of NSAID and analgesic drug administration in infants.